Application of a force model adapted for the precise turning of various metallic materials - Horváth, Richárd (Strojniški vestnik, 2017)
The knowledge of cutting forces is critical. They might affect the load of the machine and, in the case of fine turning, the deformation of thin and slim workpieces. The generated forces depend not only on material properties (hardness, tensile strength) and on cutting parameters, but also on the tool edge geometry, that strongly determines the geometry of the chip (thickness and width). This article deals with the application of a force model adapted for precise turning technology. Three different types of materials widely used in mass production were taken into consideration (C45 and KO36 steel types and AS12 die-cast aluminium alloy). The components of cutting force were measured in three directions (Fc, Ff, Fp) and the specific cutting forces were calculated. The main values of specific cutting forces were introduced for precision turning (k1,0,1); using this, a new force model was constructed based on the theoretical parameters of the non-deformed chip cross-section (h eq is equivalent chip thickness and l eff effective length of the edge of the tool) in case of all three examined materials. Investigations revealed that the influence of l eff on specific cutting force components is not negligible; however, it has the least effect on k c and is the most influential in case of k p . The errors of the constructed new force models follow Gaussian distribution with low values of standard deviation. Thereby, the models can be applied to estimate cutting force components during the technological process planning procedure with adequate accuracy.
Keywords: avstenitno nerjavno jeklo; evtektična aluminijeva zlitina za tlačno litje; merjenje sil; model sil; natančno struženje; nelegirano jeklo; specifična rezalna sila